Evaluation of reliability, quality, accuracy, and content of youtube videos on bruxism in children- A descriptive study - US, MAHMUT CANER (My University, 2023)
Objective: People frequently refer to the internet for information about their health problems. This study aimed to evaluate the reliability, quality, accuracy, and content of YouTube videos about bruxism in children. Material and Methods: YouTube was searched systematically using multiple and specific keywords for ‘Bruxism in Children’. The first 60 videos from each keyword search were analyzed. Descriptive data were recorded. Videos were categorized and scored according to publishers. Researchers evaluated the reliability of the videos by using the modified DISCERN, the quality of the videos by using the Global Quality Score (GQS), and accuracy of the videos by using the Journal of the American Medical Association (JAMA) benchmark criteria and the contents of the videos. Results: A total of 80 videos meeting the inclusion criteria were included in the study. The average values of JAMA, DISCERN, and GQS were 1.3/4.00, 2.4/5.00, and 2.8/5.00, respectively. The contents of 35 videos were non-comprehensive. According to the contents, the median values differed in the DISCERN and GQS (p<0.001), but not in JAMA (p=0.812). The median value of the DISCERN, GQS, and Content scores in comprehensive videos were all higher (p<0.001). According to individual users, the median DISCERN, GQS, and Content values were lower (p=0.006, p=0.004, p=0.015), and the median interaction index value was higher (p=0.010). Conclusion: YouTube may not be considered a completely reliable source of information on bruxism in children. Health professionals should be encouraged to create and publish more comprehensive, reliable, and accurate videos on bruxism in children.

Amaç: İnsanlar sağlık sorunları hakkında bilgi almak için sıklıkla internete başvururlar. Bu çalışmanın amacı, çocuklarda bruksizm ile ilgili YouTube videolarının güvenilirliği, kalitesi, doğruluğu ve içeriğini değerlendirmektir. Gereç ve Yöntemler: YouTube’taki videolar ‘Çocuklarda Bruksizm’ için birden fazla ve spesifik anahtar kelime kullanılarak sistematik olarak arandı. Her bir anahtar kelime aramasından ilk 60 video analiz edildi. Tanımlayıcı veriler kaydedildi. Videolar yayıncılara göre kategorilere ayrıldı ve puanlandırıldı. Videoların güvenilirliği modifiye DISCERN, kalitesi Global Quality Score (GQS), doğruluğu Journal of the American Medical Association (JAMA) benchmark kriterleri ve içerikleri belirlenen kriterler göre değerlendirdi. Bulgular: Dahil edilme kriterlerini karşılayan toplam 80 video çalışmaya dahil edildi. JAMA, DISCERN ve GQS’ in ortalama değerleri sırasıyla 1.3/4.00, 2.4/5.00 ve 2.8/5.00 idi. 35 videonun içeriği kapsamlı değildi. İçeriğe göre, medyan DISCERN ve GQS skorları farklılık gösterirken (p<0,001) JAMA’da farklılık görülmedi (p=0,812). Kapsamlı videolarda DISCERN, GQS ve Content puanlarının medyan değeri daha yüksekti (p<0,001). Bireysel kullanıcılara göre medyan DISCERN, GQS ve Content değerleri daha düşük (p=0,006, p=0,004, p=0.015) ve medyan etkileşim indeks değeri daha yüksekti (p=0,010). Sonuç: YouTube, çocuklarda bruksizm hakkında tamamen güvenilir bir bilgi kaynağı değildir. Sağlık profesyonelleri çocuklarda bruksizm hakkında daha kapsamlı, güvenilir ve doğru videolar oluşturmaya ve yayınlamaya teşvik edilmelidir.
Çocuklarda bruksizmle ilgili youtube videolarının güvenilirliği, kalitesi, doğruluğu ve içeriğinin değerlendirilmesi- tanımlayıcı çalışma
Keywords: YouTube; Internet; Bruxism; Teeth Grinding; Children; İnternet; Bruksizm; Diş gıcırdatma; Çocuk